Tecnologías de la información y la comunicación en el área de estudios sociales para el séptimo año de educación básica, año 2014 - Villarreal Pallo, Carla Nila (2015)
Actually, ICT is an important resource in the teaching and learning process; that is the reason because of this research is proposed to create an interactive CD for the subject of Social Studies at the Seventh Year of Basic Education. The principal objective is intended students to have a meaningful learning by taking into account the importance of technology in the classroom. In order to design the CD, the interactivity was considered as an important element that produces interest in learning owing to the fact that is an innovative technological resource for the entire educational society. The used methodology is a documentary-bibliographical research in a descriptive way. The data collected was applied in acquiring a number of ideas that served to structure the design of the interactive CD, so a technological tool is presented for the benefit of students. Moreover, it will help students to pay more attention, interest and motivation during the subject classes.